Characterization of the responses of cork oak (Quercus suber) to iron deficiency (Tree Physiology, 2001)
We studied responses of cork oak (Quercus suber L.) to iron (Fe) deficiency by comparing seedlings grown hydroponically in nutrient solution with and without Fe. Seedlings grown without Fe developed some responses typical of the Strategy I group of Fe-efficient plants, including two- and fourfold increases in plasma membrane ferric chelate reductase activity of root tips after 2 and 4 weeks of culture in the absence of Fe, respectively. Moreover, seedlings grown hydroponically for 2 weeks without Fe caused marked decreases in the pH of the nutrient solution, indicating that root plasma membrane ATPase activity was induced by Fe deficiency. Iron deficiency also caused marked decreases in leaf chlorophyll and carotenoid concentrations, and chlorophyll concentrations were decreased more than carotenoid concentrations. Iron deficiency resulted in an 8% decrease in the dark-adapted efficiency of photosystem II and a 43% decrease in efficiency of photosystem II at steady-state photosynthesis. No major root morphological changes were observed in seedlings grown without Fe, although seedlings grown in Fe-deficient nutrient solution had light-colored roots in contrast to the dark brown color of control roots.
10.1093/treephys/21.18.1335